Biliary, pancreatic or duodenal cancer in carriers of biliodigestive anastomoses previous due to non-neoplastic pathology - Praderi, Raúl C; Harretche, Martín; Chiossoni, Martha; Retich, Gisela; Navarrete, Héctor; Beguiristain, Alberto; Gutiérrez Galiana, Horacio; Juambeltz, Nelson; Iacopino, Julio; Dutto, Gabriel; Odriozola, Martín (Cirugía del Uruguay, 1992)
The authors present the clinical histories of tour patients; three of them had been operated on because of biliary lithiasis by other surgeons. Two of the ones with choledochal stones had been treated by means of choledocho--duodenostomy and years la ter one developed cancer of the choledochus and the other duodenal cancer. The patient whose choledochus was bound underwet a hepato-jejunostomy and was readmitted the fol/owing year with cancer of the pancreas head which obviously did not resu/t in jaundice.